Potential anti-cancer effect of N-hydroxy-7-(2-naphthylthio) heptanomide (HNHA), a novel histone deacetylase inhibitor, for the treatment of thyroid cancer. Issue 1 (December 2015) - Kim, Seok-Mo; Park, Ki-Cheong; Jeon, Jeong-Yong; Kim, Bup-Woo; Kim, Hyeung-Kyoo; Chang, Ho-Jin; Choi, Seung-Hoon; Park, Cheong-Soo; Chang, Hang-Seok
Abstract Background Thyroid cancer has been indicated to have a higher global proportion of DNA methylation and a decreased level of histone acetylation. Previous studies showed that histone gene reviser and epigenetic changes role significant parts in papillary and anaplastic thyroid cancer tumorigenesis. The goal of this research was to study the endoplasmic reticulum (ER) stress-mediated actions of the dominant histone deacetylase (HDAC) inhibitor, N-hydroxy-7-(2-naphthylthio) hepatonomide (HNHA), in thyroid cancer and to explore its effects on apoptotic cell death pathways. Methods Experiments were achieved to conclude the effects of HNHA in papillary thyroid cancer (PTC) and anaplastic thyroid cancer (ATC) cell lines and xenografts, as compared with two other established HDAC inhibitors (SAHA; suberoylanilide hydroxamic acid and TSA; trichostatin A). Results Apoptosis, which was induced by all HDAC inhibitors, was particularly significant in HNHA-treated cells, where noticeable B-cell lymphoma-2 (Bcl-2) suppression and caspase activation were observed both in vitro and in vivo. HNHA increased Ca2+ release from the ER to the cytoplasm. ER stress-dependent apoptosis was induced by HNHA, suggesting that it induced caspase-dependent apoptotic cell death in PTC and ATC. PTC and ATC xenograft studies demonstrated that the antitumor and pro-apoptotic effects of HNHA were greater than those of the established HDAC inhibitors. These HNHA activities reflected its induction of caspase-dependent and ER stress-dependent apoptosis on thyroid cancer cells. Conclusions The present study indicated that HNHA possibly provide a new clinical approach to thyroid cancers, including ATC.